PENGEMBANGAN HIDROGRAF SATUAN SINTETIK NAKAYASU DAN GAMA I TERHADAP HIDROGRAF SATUAN OBSERVASI DI DAS KATINGAN - Ari Satria Prabowo (Lambung Mangkurat University Press, 2014)
This thesis discuss about the development of synthetic unit hydrograph based on Katingan watershed. There are two synthetic unit hydrograph developed in this research, they are synthetic unit hydrograph of Nakayasu and Gama I, both produce different hydrograph toward observation hydrograph in Katingan watershed. Nakayasu and Gama I are developed to produce synthetic unit hydrograph that comes in accordance with observation unit hydrograph. The two hydrographs are developed by changing constants of peak discharge (TR) and recession coefficient (K) and making squares calculations at the time when the line peaked for Gama I, and changing constants in calculations when the graphics decline for Nakayasu The development of the synthetic unit hydrograph of Nakayasu and Gama I results in hydrograph which is closer to the observation hydrograph. The result can be seen from the smaller error percentage value in Nakayasu as much as 7.97 percent from the initial value of 89.85 percent and 68.11 percent in Gama I from the initial value of 392.63 percent.